Red panda : biology and conservation of the first panda - Glatston, A. R. (Academic Press, 2022)
Red Panda: Biology and Conservation of the First Panda, Second Edition, provides the most up-to-date research, data, and conservation solutions for the red pandas, Ailurus species. Since the publication of the previous edition, the International Union for Conservation of Nature (IUCN) updated the threat level of red pandas, and they are now considered to be endangered. This latest edition is updated to provide an in-depth look at the scientific and conservation-based issues urgently facing the red panda today. Led by one of the world's leading authorities and advocates for red panda conservation, this new edition includes data from the Population and Habitat Viability (PHVA) workshops conducted in three of the species' range states, Nepal, China, and India; these workshops utilized firsthand information on the decrease of red panda populations due to factors including deforestation, illegal pet trade, human population growth, and climate change. This book also includes updated information from the first edition on reproduction, anatomy, veterinary care, zoo management, and fossil history.